(untitled) (Italian Journal of Public Health, 2003)
Osservasalute is the Italian Health Observatory (http://www.osservasalute.it) and it is aimed to study performances of regional health systems, to monitor quality of care in the Italian regions, to disseminate the main results of these activities and provide information to support decisions and choices of health programs and the allocation of resources.[1] In 2004 Osservasalute has published the results of its activity in the Osservasalute report 2004. A critical analysis of the data reported has revealed some phenomena of particular interest: 1. the good health of the Italian population; 2. the remarkable improvements obtained in last the 10-20 years, accompanied by a substantial reduction in regional differences; 3. a good level of regional health services; 4. the persistence of geographical variations; 5. the risk of incoherent and disconnected policy planning between several of the regions.